Critical Land Planning Low Emission Development Strategy in Bila Riven Basin of South Sulawesi Province - Sultan; Khaifah Asgaf; Sri Ade Putra; Muthmainnah; Mukhlis (Jurnal Penelitian Pendidikan IPA, 2026)
Environmental degradation in the Bila Watershed, characterized by increasing critical land, carbon emissions, erosion, and sedimentation in Lake Tempe, requires integrated low-emission land-use planning. This study aims to analyze carbon stocks, carbon dioxide (CO₂) sequestration, sedimentation, and economic valuation under several land-use scenarios using the Land Use Planning for Low Emission Development Strategy (LUWES) approach. The novelty of this study lies in the integration of critical land analysis, carbon stock estimation, sedimentation assessment, and economic valuation into low-emission watershed planning scenarios. The research was conducted in the Bila Watershed, South Sulawesi Province, covering an area of 179,612.87 ha during the 2016–2017 period. Biomass measurements were conducted using nested plots across representative land-cover classes, while erosion was estimated using the Universal Soil Loss Equation (USLE) and sedimentation was calculated using the Sediment Delivery Ratio (SDR) approach. Economic feasibility was analyzed using the Net Present Value (NPV) method. Three land-use scenarios were simulated over a 20-year planning horizon. The results indicate that the existing condition produced carbon emissions of 915,537.49 tons CO₂-eq and estimated sedimentation of 396,163.05 tons/year. Scenario I provided the best ecological-economic balance by increasing carbon stocks, reducing erosion and sedimentation by 45.93%, and increasing economic value by 10.66%. Scenario II generated the highest economic return but increased ecological pressure, while Scenario III emphasized social forestry and emission reduction with moderate economic benefits. These findings demonstrate that integrated low-emission watershed planning can support critical land rehabilitation, climate change mitigation, and sustainable watershed management.